Real-World Decision Support Systems: Case Studies - Papathanasiou, Jason; Ploskas, Nikolaos; Linden, Isabelle (Integrated Series in Information Systems, 2016)
This book presents real-world decision support systems, i.e., systems that have been running for some time and as such have been tested in real environments and complex situations;